Clinicopathological correlations in cor pulmonale. Issue 7 (July 1992) - Calverley, P M; Howatson, R; Flenley, D C; Lamb, D
Abstract : BACKGROUND: The relation between pulmonary disease and physiological abnormality in patients with hypoxic cor pulmonale is controversial and the association between arterial hypoxaemia and right ventricular hypertrophy has been challenged. To address these problems matched patients treated with and without domiciliary oxygen were studied. METHODS: Necropsy data were obtained on 19 patients (14 male), 10 of whom had been treated with domiciliary oxygen. Pulmonary artery pressure and total pulmonary vascular resistance as well as blood gas tensions during the breathing of air and oxygen were available for the six months before death. Formalin fixed lung slices were assessed for panacinar and centriacinar emphysema. Right and left ventricular weights were measured and their ratio (LV&S/RV) was used as an index of right ventricular hypertrophy. Carotid body weights were available in 14 cases. RESULTS: Fourteen patients died of respiratory failure and antemortem thrombus was found in the pulmonary arteries of eight cases. Physiological measurements were unrelated to the degree of macroscopic emphysema, pulmonary hypertension, or daytime blood gas tensions. When allowance was made for the higher "ambient" arterial oxygen tension (PaO2) of those who had oxygen, PaO2 was correlated with LV&S/RV (r = 0.79), absolute right ventricular weight (r = -0.53), and carotid body weight (r = 0.68). CONCLUSIONS: These data show that in hypoxic cor pulmonale in vivo physiological disturbances are poor indicators of the underlying disease process. The relation of "ambient" PaO2 to right ventricular hypertrophy and carotid body weight suggests that domiciliary oxygen therapy might lead to regression of such established disease.